Malaysia IT outsourcing industry: practices, models, trends and challenges from a case of an offshore global service provider - Ahlan, Abdul Rahman; Suhaimi, Mohd Adam; Hussin, Husnayati; Arshad, Yusri (WSEAS Press, 2009)
Malaysia IT outsourcing (ITO) practices have been around after the Kodak effect but was not widely publicized until massive public sector computerization projects and automation of financial systems after Asian financial crisis in 1997. Thus, many service providers, including world-class firms, providing ITO business models can be found in operating in Malaysia. ITO models evolve from traditional to innovation phase in 2010 onwards. One of the innovative models in Malaysia is the global offshore service delivery model which is based on four pillars, namely: Experienced Leadership; Global Best Practice; Human Capital; Domain Knowledge. To be able to compete globally, Malaysia has equipped its companies with higher capabilities and competencies via international certifications and continuous skills developments. Several advantages proposed by Malaysia include: economic stability, political stability, multi-lingual, world-class infrastructure, affordable lifestyle, value propositions and many others. In this paper, we present the detailed views of a senior executive management on two open-ended in-depth interviews and one CEO roundtable discussion.